Pemasaran Politik dan Keputusan Memilih Partisipan Pemilihan Kepala Daerah pada Kelompok Perkotaan dan Kelompok Pinggiran Kota (Studi pada Kelompok Partisipan Politik di Kota Pekanbaru) - Alwie, Alvi Furwanti; Thoyib, Armanu; Zain, Djumilah; Surachman, Surachman (Jurnal Aplikasi Manajemen, 2011)
Political marketing is necessary both for politicians and political parties. Political marketing is believed to be the methods and instruments that can help politicians and political parties in order to create competitive advantage and win the competition. Actually there are some similarities in terms of selling politicians and to sell products. Most political sell products in the shape of abstracs and intangible, related to the value (value laden), the promise in the future, or something that satisfaction gained in the long term, vague, and uncertain. The purpose of this study was to find out level of perceptions of urban and suburban groups on the political product, the price of politics, political campaigns, and political distribution of the decisions to vote at the urban and suburban groups, as well as examine the differences between urban groups with a group of suburban. This study sampled at village of Cintaraja and the village of Kulim in the city of Pekanbaru by respondents as many as 100 people. The data used are primary data obtained from a questionnaire with five-point Likert scale to determine the perceptions of respondents on the variables observed. The findings obtained are known effect of a political product, the price of politics, poltical campaigns and political distribution in the urban and suburban groups. Political campaign and the distribution of politics does not affect the vote decision of urban group. On the outskirts of the distribution of political groups does not affect the decision to choose, there is a different partially, but simultaneously, there is no difference in the decision to vote in urban with a group of suburban.